NATURAL RESOURCES FROM PLANTS IN THE TREATMENT OF CANCER: AN UPDATE - Tripathi, Parul; Singh, Aditi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Cancer has become the second leading cause of death worldwide. The incidences of cancer are rising at an alarming rate but it can be reduced and controlled by evidence-based strategies for cancer prevention, early detection, and management of patients with cancer. Historically, it is proven that plants and their metabolites have great potential in the treatment of various acute diseases as well as chronic disorders. The novel bioactive compounds from many plants are being studied as potential therapeutic agents because of their high activity and low toxicity. This review gives a comprehensive description of such medicinal plants which have been studied as potentially effective against cancer.